Comparative study of inguinal versus scrotal approach in idiopathic vaginal hydrocele. - Agnihotri, Ishan Prafulla; Jain, S. C.; Swarnkar, Manish M. (International Surgery Journal, 2018)
Background: Hydrocele is a common cause of painless scrotal swelling worldwide. Methods: Hydrocele is a common cause of painless scrotal swelling worldwide. This prospective study was carried out at AVBRH, Sawangi Wardha, Maharashtra, India with the aim of comparing scrotal and inguinal approaches of hydrocelectomy. 100 patients were enrolled between September 2015 and September 2017 and were randomly selected for inguinal and scrotal approaches (n=50 each). They were compared on the basis of volume of hydrocele sac, operative time, post-operative hospital stay, post-operative complications, number of doses of injectable analgesia required and time of return to daily life activity. Results: The patients’ age ranged from 23 to 65 years (42.80±9.73 years) in the inguinal approach group and 22 to 65 years (41.30±11.21 years) in the scrotal approach group. Operative time in the scrotal approach group was less and was associated with more post-operative complications (pain and scrotal edema being frequent), longer hospital stay, increased requirement of injectable analgesia dosage. On the other hand, inguinal approach group had a marginally longer operative time and was associated with less post-operative pain, none to minimal complications, less hospital stay and early return to daily life activities. Conclusions: Thus, hydrocelectomy by inguinal approach is an effective alternative method for the treatment of idiopathic hydrocele.